2009
DOI: 10.1152/ajpheart.00528.2009
|View full text |Cite
|
Sign up to set email alerts
|

T-type calcium channels are regulated by hypoxia/reoxygenation in ventricular myocytes

Abstract: Pluteanu F, Cribbs LL. T-type calcium channels are regulated by hypoxia/reoxygenation in ventricular myocytes. Am J Physiol Heart Circ Physiol 297: H1304 -H1313, 2009. First published August 7, 2009 doi:10.1152/ajpheart.00528.2009.-Low-voltageactivated calcium channels are reexpressed in ventricular myocytes in pathological conditions associated with hypoxic episodes, but a direct relation between oxidative stress and T-type channel function and regulation in cardiomyocytes has not been established. We aimed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
31
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 51 publications
0
31
1
Order By: Relevance
“…However, a recent study confirmed that, in rat neonatal ductus arteriosus, ␣ 1G mRNA and protein are not changed under hypoxia (1% O 2 ) but rather upregulated significantly under oxygenation (1). Consequently, these seemingly conflicting data support the idea that hypoxia differentially modulates T-type Ca 2ϩ channels depending on cells type as stated previously (31).…”
Section: Discussionmentioning
confidence: 60%
See 2 more Smart Citations
“…However, a recent study confirmed that, in rat neonatal ductus arteriosus, ␣ 1G mRNA and protein are not changed under hypoxia (1% O 2 ) but rather upregulated significantly under oxygenation (1). Consequently, these seemingly conflicting data support the idea that hypoxia differentially modulates T-type Ca 2ϩ channels depending on cells type as stated previously (31).…”
Section: Discussionmentioning
confidence: 60%
“…Similarly, when cardiac ventricular myocytes were subjected to hypoxia/reoxygenation, both ␣ 1G and ␣ 1H were shown to be differentially regulated, with a decrease in ␣ 1G mRNA and an increase in ␣ 1H mRNA (31). Additionally, the observation that ␣ 1H is upregulated under hypoxia is in agreement with the presence of several potential hypoxia-inducible factor (HIF) binding sites within the 5=-flanking region of the gene.…”
mentioning
confidence: 58%
See 1 more Smart Citation
“…ated cardiac hypertrophy, we used cultured NMVMs, which are known to endogenously express the I Ca, T (11,31,32). Cultured NMVMs were treated with Ang-II (10 mol/liter) or vehicle for 48 h, and I Ca, T was measured.…”
Section: Cav-3 Knockdown Results In Increased Ang-ii Stimulation Of Imentioning
confidence: 99%
“…It is known too, that CoCl 2 serves as hypoxia-dependent factor [7,26,27], and endothelial cells respond to hypoxia by decreasing the degradation of hypoxia-inducible factor 1α. The accumulation of last leads to increase transcription of numerous proteins involved in cell growth and survival [28], that may cause the increase of EEl activity, synthesized by endothelial cells.…”
Section: Discussionmentioning
confidence: 99%